Three-Dimensional Digital Models for Rating Dental Arch Relationships in Unilateral Cleft Lip and Palate. (March 2013) - Chawla, O.; Atack, N.E.; Deacon, S.A.; Leary, S.D.; Ireland, A.J.; Sandy, J.R.
Objective: To determine the reliability and reproducibility of using three-dimensional digital models as an alternative to plaster models for rating dental arch relationships in patients born with unilateral cleft lip and palate. Design: Reliability and reproducibility study. Methods: Study models of 45 patients born with unilateral cleft lip and palate were made available in plaster and three-dimensional digital models. Records were scored a week apart by three examiners using the 5-year-olds' index reference models in the same two formats as the patient models. To assess reproducibility the study was repeated 4 weeks later under similar conditions to minimize the influence of memory bias on the results. The reliability of using the three-dimensional digital models was determined by comparing the scores for each examiner with the plaster model scores. Results: Weighted kappa statistics indicated repeatability for the plaster models was very good (.83 to .87). For the three-dimensional digital models it was good to very good (.74 to .83). Overall, the use of the three-dimensional digital models showed good agreement with the plaster model scores on both occasions. Conclusion: Three-dimensional digital models appear to be a good alternative to plaster models for assessing dental arch relationships using the 5-year-olds' index.